2022
DOI: 10.1101/2022.09.02.506400
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Zinc Fingers and Homeoboxes 2 is Required for Diethylnitrosamine-induced Liver Tumor Formation in C57BL/6 Mice

Abstract: Liver cancer, comprised mainly of hepatocellular carcinoma (HCC), is the third leading cause of cancer deaths worldwide and increasing in Western countries. We previously identified the transcription factor Zinc Fingers and Homeoboxes 2 (Zhx2) as a regulator of hepatic gene expression, and many Zhx2 target genes are dysregulated in HCC. Here, we investigate HCC in Zhx2-deficient mice using the Diethylnitrosamine (DEN)-induced liver tumor model. Our study using whole-body Zhx2 knock-out (Zhx2KO) mice revealed t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Some literature reported that ZHX2 may be related to apoptosis (35,37). There are also some literature reports that ZHX2 overexpression can promote proliferation and migration and inhibit apoptosis (40)(41)(42). Studies have shown that ZHX2 improves atherosclerosis by regulating macrophage apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Some literature reported that ZHX2 may be related to apoptosis (35,37). There are also some literature reports that ZHX2 overexpression can promote proliferation and migration and inhibit apoptosis (40)(41)(42). Studies have shown that ZHX2 improves atherosclerosis by regulating macrophage apoptosis.…”
Section: Discussionmentioning
confidence: 99%